(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
In Argentina, the beginning of the production of photographic shots generated by the Ministry of Public Works at the beginning of the 19th century had the purpose of registering the public work as a sample of a work planned, carried out and audited by the State. Government agencies were in charge of promoting an image of the building reforms in order to show the "modernities" that were being built in the name of progress, finding in this format the most appropriate means to graphically exemplify reality (Harasic; Troisi 2014) . As well as, it includes an early incorporation into the educational field due to its wide possibilities of documentation of the school context. In this way, using these shots as a historical source allows us to recognize the symbolic and material configurations, thus exhibiting not only reality but also the silent ways of educating (Martins, 2019). It is from this perspective that in the present work we analyze part of the documentary set of the photographic batch corresponding to the survey of the work that included the construction of the Mixed Normal School of Río Cuarto, between 1905 and 1926 when the arrival of school furniture concluded. Attending to the complementation of photography with written sources that allows us to reconstruct the empirical dimension of school culture (Escolano Benito, 2004) in the city of Río Cuarto at the beginning of the last century.